Investigation of sodium and germanium bi-substituted trimeric strontium silicate (Sr3-3xNa3xSi3-3yGe3yO9-δ; 0 < x < 0.20, y = 0.1) as solid electrolyte - Tarique H.; Shahid R.; Singh P.; Singh A.K.; Pandey R.; Singh P. (My University, 2025)
Abstract: Strontium silicates doped with an alkali metal are extensively investigated after their high conductivity reported in the moderate range of temperature (773 K < T < 1073 K). This work aims to study the structural, microstructural, morphological, thermal, and electrical investigation of Sr3-3xNa3xSi3-3yGe3yO9-δ (0 < x < 0.20, y = 0.1; SNSG) system. A solid-state reaction method was adopted for synthesis of the compositions. Composition's phase formation was examined using X-rays Rietveld refinement techniques. X-Ray Diffraction (XRD) patterns were mapped by the monoclinic symmetry having space-group C12/c1. Moreover, along with monoclinic phase a few minor peaks of Sr2SiO4 were also detected along with prominent peaks of parent SrSiO3. To comprehend the surface morphology of the compositions, scanning electron microscopy has been employed. Studies using Fourier transform infrared spectroscopy and Raman spectroscopy have been carried out to investigate the characteristic bands and vibrations modes of the system. Characteristic valence states of constituent elements and stability of the sintered samples in air were confirmed by the X-ray Photoelectron Spectroscopy (XPS) analysis. The electrical behavior of this system was studied by electrochemical impedance spectroscopy (EIS) techniques. Electrical conductivity of the platinum-coated sintered pellet samples was also calculated to check its feasibility as a cost-effective electrolyte for intermediate temperature range. It has also been observed that in Na-doped compositions, a few amorphous phases of Sodium silicate (Na2Si2O5) formed as impurity that may contribute to the total conductivity. Graphical Abstract: (Figure presented.) © The Author(s), under exclusive licence to Springer Nature B.V. 2023.